PRISONER EQUALITY: A STUDY OF PRISONER CLASSIFICATION SCHEMES - Sinprasitkul, Wichet (Rangsit Journal of Law and Society, 2022)
Although being detained under the state power, the convict punished by the judicial decisions, are protected in the light of the above legal principles as well. However, section 52 (2) of the Corrections Act B.E. 2560 classifies the prisoners which affects the convicts. Therefore, this research aims to study and analyze 1). the principle of equality related to the prisoners in Thailand 2). The problems derived from the above classification under section 52 (2) of the Corrections Act B.E. 2560 3). The laws concerning the classification of the convicts in the Federal Republic of Germany, Japan, the United Kingdom, and other nations related to Thailand. According to the findings, as the punishment and the period of time for the convicts have already been determined in accordance with the level of the malignance and severity of their actions, all of the prisoners in the prisons should be equally recognized as ‘a convict by the judgement of the court. Therefore, this research proposes that the corrections law should not categorize the prisoners, and there should be a punishment plan and behavioral assessment individually for each convict, in order to truly comply with the principles regarding the rule of law, the human rights, and the human dignity, as expressed in the laws of myriad nations that no longer have the prisoner classification. For example, the Federal Republic of Germany, Japan and the United Kingdom etc.